2011
DOI: 10.2147/ijn.s25842
|View full text |Cite
|
Sign up to set email alerts
|

Coupling technique of random amplified polymorphic DNA and nanoelectrochemical sensor for mapping pancreatic cancer genetic fingerprint

Abstract: Objective To review the feasibility of coupling the techniques of random amplified polymorphic DNA (RAPD) with carbon nanotube-based modified electrode for guanine/deoxyguanine triphosphate (dGTP) electrochemical sensing for mapping of the pancreatic cancer genetic fingerprint and screening of genetic alterations. Methods We developed a new method to study the electrochemical behavior of dGTP utilizing carbon multiwalled nanotube (MWNT)-modified glassy carbon electrodes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…At the early stages of pregnancy, very small amounts of fetal cells in the maternal blood can be used for genetic defect diagnosis (Bianchi and Hanson, 2006). Liu et al (2011) developed a new method to study the electrochemical behavior of dGTP utilizing carbon multi-walled nanotube-modified glassy carbon electrodes for mapping of the pancreatic cancer genetic fingerprint and screening of genetic alterations. Their results indicated that the coupling of random amplified polymorphic DNA and nanoelectrochemical sensors could be successfully applied to the screening of genetic alterations in pancreatic cancer and for mapping of DNA fingerprints.…”
Section: Unique Physical and Chemical Properties Of Nanomaterialsmentioning
confidence: 99%
“…At the early stages of pregnancy, very small amounts of fetal cells in the maternal blood can be used for genetic defect diagnosis (Bianchi and Hanson, 2006). Liu et al (2011) developed a new method to study the electrochemical behavior of dGTP utilizing carbon multi-walled nanotube-modified glassy carbon electrodes for mapping of the pancreatic cancer genetic fingerprint and screening of genetic alterations. Their results indicated that the coupling of random amplified polymorphic DNA and nanoelectrochemical sensors could be successfully applied to the screening of genetic alterations in pancreatic cancer and for mapping of DNA fingerprints.…”
Section: Unique Physical and Chemical Properties Of Nanomaterialsmentioning
confidence: 99%